Analisis Yuridis Pemberian Alat Kontrasepsi Bagi Anak Usia Sekolah Dan Remaja Studi Terkait Pelaksanaan Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan Pada Peraturan Pemerintah Nomor 28 Tahun 2024 - Hayyu Nurrafi Awalsari; Radian Syam (PT. Hasba Edukasi Mandiri, 2025)
The provision of contraceptives for school-age children and adolescents is a complex issue, especially related to legal and social aspects. This study analyzes government policies regarding the provision of contraceptives in this age group based on Government Regulation No. 28 of 2024 which implements Law No. 17 of 2023 concerning Health. The policy aims to support reproductive health, prevent sexually transmitted diseases, and reduce teen pregnancy rates. The method used is a normative juridical approach, analyzing regulations and literature related to the perspective of legal ideals which are the fundamental principles that are the basis for the formation and implementation of laws and regulations. The results show that although this policy aims to protect the health of children and adolescents, this policy does not meet the aspect of the law itself and has no further explanation In conclusion, this policy needs to be adjusted to the principles of legal ideals, especially in terms of legal certainty and utility. The recommendations include the evaluations in terms of contraceptive services.